A Wearable Microneedle‐Based Extended Gate Transistor for Real‐Time Detection of Sodium in Interstitial Fluids (Adv. Mater. 10/2022). Issue 10 (10th March 2022) - Zheng, Youbin; Omar, Rawan; Zhang, Rongjun; Tang, Ning; Khatib, Muhammad; Xu, Qi; Milyutin, Yana; Saliba, Walaa; Broza, Yoav Y.; Wu, Weiwei; Yuan, Miaomiao; Haick, Hossam
Abstract : Biosensors In article number 2108607, Miaomiao Yuan, Hossam Haick, and co‐workers report an innovative, stretchable, skin‐conformal, fast‐response, microneedle, extended‐gate field‐effect transistor biosensor for real‐time detection of sodium in interstitial fluids for minimally invasive health monitoring. High sensitivity, low limit of detection, excellent biocompatibility, and on‐body mechanical stability are demonstrated. This platform can be integrated with a wireless‐data transmitter and the Internet‐of‐Things cloud for real‐time monitoring and long‐term analysis.